The Study of Recycled High-Density Polyethylene Reinforce Polyurethane (HDPE-PU) Foam for Automotive Seat Cover Application - Alias, Mohamad Azmeer; Marsi, Noraini (Progress in Engineering Application and Technology, 2022)
One of the key concerns of automotive manufacturers is the NVH issue. Furthermore, corporations are increasingly confronted with the challenge of finding alternative solutions for disposing of significant volumes of packaging. As an outcome, this study proposes a solid-state recycling approach that includes direct recycling of polyethylene as a green engineering shaping technology. The purpose of this research is to find the best HDPE plastic waste reinforced PU foam composition for automotive seat applications. Recycled High-density polyethylene (HDPE) plastic waste can provide new possibilities for a smoother, quieter driving experience while also addressing the issue of materials that contribute to overall vehicle weight. High-density polyethylene (HDPE) plastic waste is prepared for the various ratio of 5, 10, 15, and 20 (wt/wt%). The mechanical properties tests were carried out by Tensile test (ASTM D3574), and Impact test (ASTM D3574). For physical properties test by density test, and porosity test (ASTM C20-00), leaching test (ASTM D6234), and Optical Microscopic (OM) test (ASTM F728-81) was performed. The result showed that the highest strength of tensile strength is 3.68506 N/m2 while young modulus strength is 62.95083 MPa. Furthermore, the maximum impact test was 1.06 kJ/m2. The density and porosity test results show the highest average density with 0.286 g/cm3 and the highest with 0.17% of average porosity. Insulation foams were also investigated under an optical microscope and found to alter in white, homogeneous morphological shape, and cellular form as the percentage of plastic to PUF increased. The optimum composition of recycled High-Density Polyethylene reinforced Polyurethane (HDPE-PU) foam with 10 (wt/wt%) is possible to be applied for automotive seat cover application.